Adapting the education system of the ship’s electricians to the modern technology and organization of work on board - Kamiński, K.; Galbas, J. (Scientific Journal of Gdynia Maritime University, 2017)
Significant changes in marine technologies and work organization on board modern ships took place in the recent years. These changes expanded tasks and responsibilities of Electro-Technical Officers. Efficient and future oriented education process of ETOs must include these new trends in teaching programs and methodology.